The influence of heat acclimation and hypohydration on post-weight-loss exercise performance - Barley, O. R.; Chapman, D. W.; Mavropalias, G.; Abbiss, C. R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the influence of fluid intake on heat acclimation and the subsequent effects on exercise performance following acute hypohydration. Methods: Participants were randomly assigned to 1 of 2 groups, either able to consume water ad libitum (n=10; age 23 [3] y, height 1.81 [0.09] m, body mass 87 [13] kg; HAW) or not allowed fluid (n=10; age 26 [5] y, height 1.76 [0.05] m, body mass 79 [10] kg; HANW) throughout 12×1.5-h passive heat-acclimation sessions. Experimental trials were completed on 2 occasions before (2 baseline trials) and 1 following the heat-acclimation sessions. These sessions involved 3 h of passive heating (45°C, 38% relative humidity) to induce hypohydration followed by 3 h of ad libitum food and fluid intake after which participants performed a repeat sled-push test to assess physical performance. Urine and blood samples were collected before, immediately, and 3 h following hypohydration to assess hydration status. Mood was also assessed at the same time points. Results: No meaningful differences in physiological or performance variables were observed between HANW and HAW at any time point. Using pooled data, mean sprint speed was significantly (P?<?.001) faster following heat acclimation (4.6 [0.7] s compared with 5.1 [0.8] s). Furthermore, heat acclimation appeared to improve mood following hypohydration. Conclusions: Results suggest that passive heat-acclimation protocols may be effective at improving short-duration repeat-effort performance following acute hypohydration.